Propagation material borne fungus pathogens causing early stock decay in vineyards - Dula, T. (International Journal of Horticultural Science, 2011)
A decline, a slow or sudden decay of vine trunks can occur in any phase of trunk life. In senescent or old plantages the increase in trunk decay is quite common but it is unacceptable in young plantage in their best production years.All over the world as well as in Hungary, a drastic decay of young trunks in nurseries and new plantages have caused panic in the past decades. From among the numerous fungal pathogens which are responsible for considerable financial and yield losses and threaten stock vigour Petri disease, esca and Black foot are the most important. In young decaying plants the fungal species Phaeomoniella chlamydospora, Phaeoacremonium spp. and Cylindrocarpon spp. were the most frequent while other fungi causing different trunk diseases, cancer or decay, like Eutypa lata, Botryosphaeria spp. and Fomitiporia mediterranea were also found. The most important infection source is the infected propagation material. Infection is systematic, the disease process is latent, diseased plants cannot be cured, thus, prevention is the only answer to the challenge.